2020
DOI: 10.1001/jamanetworkopen.2020.2072
|View full text |Cite|
|
Sign up to set email alerts
|

Economic Evaluation of Chimeric Antigen Receptor T-Cell Therapy by Site of Care Among Patients With Relapsed or Refractory Large B-Cell Lymphoma

Abstract: IMPORTANCE Chimeric antigen receptor (CAR) T-cell therapies are currently administered at a limited number of cancer centers and are primarily delivered in an inpatient setting. However, variations in total costs associated with these therapies remain unknown. OBJECTIVE To estimate the economic differences in the administration of CAR T-cell therapy by the site of care and the incidence of key adverse events. DESIGN, SETTING, AND PARTICIPANTS A decision-tree model was designed to capture clinical outcomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 47 publications
1
64
1
Order By: Relevance
“…The cells are then administered, and patients are monitored for a period ranging from several days to weeks depending on the complications and toxicity that arise. While outpatient therapy has been described and may be associated with increased cost savings, therapy is primarily delivered as an inpatient with some authors advocating for an observation period of at least 9 days [ 7 , 8 ]. To date, there are no published cases of significant dosing errors, intentional overdose, or toxicity related to infusion rate errors.…”
Section: Methodsmentioning
confidence: 99%
“…The cells are then administered, and patients are monitored for a period ranging from several days to weeks depending on the complications and toxicity that arise. While outpatient therapy has been described and may be associated with increased cost savings, therapy is primarily delivered as an inpatient with some authors advocating for an observation period of at least 9 days [ 7 , 8 ]. To date, there are no published cases of significant dosing errors, intentional overdose, or toxicity related to infusion rate errors.…”
Section: Methodsmentioning
confidence: 99%
“…While autologous CAR19-T therapies are extremely promising, this individualized treatment still faces many challenges such as high treatment costs, lengthy vein-to-vein time due to long production processes, and potential manufacturing failures, challenging patients’ access to a life-saving treatment. Current cost estimates for CAR-T treatments are about $450,000, with the bulk of that coming from the cost of CAR-T product manufacturing (~$373,000) [ 23 , 24 ].This cost can be further increased with other CAR-T therapy-related interventions such as pre-conditioning lymphodepletion, adverse event management, and such high treatment-associated costs make CAR-T therapy less accessible to patients-in-need and pose a significant financial burden for the healthcare system to establish it as a standard-of-care for B-ALL.…”
Section: B Cell Acute Lymphocytic Leukemiamentioning
confidence: 99%
“…One of the main disadvantages of CAR-T cell therapy is its high costs. The estimated total cost of care associated with the administration of CAR-T cell therapy was $454,611 in an academic hospital inpatient setting [ 62 ]. Another study found that the median total cost of hospitalization resulting from CAR-T cell treatment was $380,052, with a median direct cost of $262,981 [ 63 ].…”
Section: Cell-based Immunotherapiesmentioning
confidence: 99%